2019
DOI: 10.1136/bmjopen-2018-026478
|View full text |Cite
|
Sign up to set email alerts
|

Methodological advantages and disadvantages of parallel and crossover randomised clinical trials on methylphenidate for attention deficit hyperactivity disorder: a systematic review and meta-analyses

Abstract: ObjectiveTo assess the methodological advantages and disadvantages of parallel and crossover designs in randomised clinical trials on methylphenidate for children and adolescents with attention deficit hyperactivity disorder (ADHD).DesignSecondary analyses of a Cochrane systematic review.Setting and participantsWe searched relevant databases up to March 2015 and included data from parallel and crossover randomised trials assessing children and adolescents up to 18 years with ADHD.InterventionsMethylphenidate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In this study, despite the small sample size, we found the significant effect of the intervention on sleep which might be because of the strong design randomized controlled trial crossover design. A study conducted by Krogh et al emphasized that the advantage of the crossover design is the need for fewer participants and resource consumption [ 42 ]. Similarly, previous studies with less sample size have found a significant effect on sleep quality [ 13 , 15 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, despite the small sample size, we found the significant effect of the intervention on sleep which might be because of the strong design randomized controlled trial crossover design. A study conducted by Krogh et al emphasized that the advantage of the crossover design is the need for fewer participants and resource consumption [ 42 ]. Similarly, previous studies with less sample size have found a significant effect on sleep quality [ 13 , 15 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above, combined with the predominantly male sample, and the fact that the sample was restricted to patients at only three medical centers in Taiwan, limit the ability to generalize our findings to a wide clinical population suffering from ADHD. Fourth, we used a two-way crossover study design without a washout period rather than a parallel study design (Krogh et al 2019 ). We took advantage of the fewer samples that such a two-way crossover study needs, as well as the ability to obtain more precise estimates of treatment effects by removing any biological and methodological variation that are present within the crossover study design (Mills et al 2009 ; Li et al 2015 ; Krogh et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we used a two-way crossover study design without a washout period rather than a parallel study design (Krogh et al 2019 ). We took advantage of the fewer samples that such a two-way crossover study needs, as well as the ability to obtain more precise estimates of treatment effects by removing any biological and methodological variation that are present within the crossover study design (Mills et al 2009 ; Li et al 2015 ; Krogh et al 2019 ). Importantly, MPH has a short half-life, short-lived effectiveness, and a very limited carryover effect, and in this context, a meta-analysis has reported that four fifths of MPH clinical trials have used a crossover design (Krogh et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods exist for including information from crossover studies in quantitative analysis (Elbourne et al, 2002); however, incorporating the result only from the first or last period of crossover studies revealed similar results in the final analysis (Krogh et al, 2019). Hence, we included the last-period result of the crossover studies in our quantitative analysis to obtain relatively unbiased data (Ding et al, 2015).…”
Section: Methodsmentioning
confidence: 99%